Comparison between disease free survival of hepatocellular carcinoma after hepatic resection in chronic hepatitis B patients with or without cirrhosis - Karjpong Techathuvanan (2018)
© 2015 Medical Association of Thailand. All rights reserved. Hepatocellular carcinoma (HCC) in chronic hepatitis B (CHB) patients can develop in those with cirrhotic and non-cirrhotic liver. Not only impairment of liver status, but also the extension of tumor and difference of pathogenesis may also affect characteristics of patient and tumor including survival and recurrence. Objective: To evaluate the disease free survival, prognostic factors and features of HCC after hepatic resection in CHB patients with and without cirrhosis. Material and Method: Two hundred fifteen HBV-related HCC patients underwent hepatic resection and were analyzed. Cirrhotic and non-cirrhotic groups were compared for differences in patient and tumor characteristics, disease-free survival including prognostic factors. Results: In comparison with cirrhotic patients, non-cirrhotic patients had more family history of HCC, more preserved liver function, were less HBeAg positive, and had lower HBV viral load. HCC characteristics in non-cirrhotic groups showed significantly larger (5.83.7 vs. 4.93.9 cm, p = 0.036) and operative data revealed that non-cirrhotic patients underwent more major surgery (50.7 vs. 18.3%, p<0.001), and had shorter hospital stay (10.88.9 vs. 8.14.3 days, p = 0.006) than cirrhotic ones. Operative time, blood loss and requirement of PRC transfusion were similar in both groups. Pathological profiles of HCC and liver parenchyma were comparable in both cirrhotic and non-cirrhotic patients. The disease-free survival of non-cirrhotic patients was longer than cirrhotic patients (Median disease free survival were 21 and 11 months respectively, p = 0.022). The independent predictive factor of lower disease-free survival of non-cirrhotic CHB patients who underwent hepatic resection was lymph node involvement (Hazard ratio (HR), 4.598. 95% confidence interval (CI), 1.1-19.212; p = 0.037) while of cirrhotic patients, factors were age >50 years old (HR, 2.998; 95% CI, 1.298-6.925; p = 0.01), multifocal tumor (HR, 5.835; 95% CI, 1.122-30.342; p = 0.036) and portal vein involvement (HR, 3.722; 95% CI, 1.121-12.353; p = 0.032). HBV treatment after HCC diagnosis was a significant predictor in the cirrhotic group by univariate analysis (p = 0.04). Conclusion: Imaging and histological findings of HCC in cirrhotic and non-cirrhotic CHB patients were not different, except for larger tumor size in non-cirrhotic patients. Lymph node involvement is the predictor of HCC recurrence in noncirrhotic CHB patients. Age >50 year old and multifocal tumor and portal vein involvement are the predictors of HCC recurrence in cirrhotic CHB patients. These groups may need surveillance that is more intensive after hepatic resection. Antiviral therapy may lower the risk of HCC recurrence among CHB cirrhotic patients.